Incidence of suboptimal response to tumor necrosis factor antagonist therapy in inflammatory bowel disease in newly industrialised countries: The EXPLORE study. Issue 8 (August 2020) - Yamamoto-Furusho, Jesus K.; Al Harbi, Othman; Armuzzi, Alessandro; Chan, Webber; Ponce de Leon, Enrique; Qian, Jiaming; Shapina, Marina; Toruner, Murat; Tu, Chia-Hung; Ye, Byong Duk; Guennec, Morgane; Sison, Cecilia; et al.
Abstract: Background: Incidence of inflammatory bowel disease (IBD) is increasing in newly industrialised countries (NICs); however, data on suboptimal response to anti-tumor necrosis factor (anti-TNF) agents are limited. Objectives: To assess incidence and indicators of suboptimal response to first anti-TNF therapy in IBD patients in NICs. Methods: A chart review was conducted in ten countries from Asia-Pacific (APAC), Latin America (LatAm), and Russia and the Middle East (RME) regions among patients diagnosed with ulcerative colitis (UC) or Crohn's disease (CD), initiating anti-TNF therapy in 2010–2015. The cumulative incidence of suboptimal response to anti-TNF therapy was assessed using the following indicators: dose escalation or discontinuation, augmentation with non-biologic therapy, IBD-related hospitalization, or surgery. Results: The study included 1, 674 patients (570 UC; 1, 104 CD). At 24 months, 32.9% of UC (APAC: 45.1%; LatAm: 38.2%; RME: 23.8%) and 41.2% of CD patients (APAC: 54.1%; LatAm: 42.5%; RME: 29.5%) had experienced suboptimal response. The most frequent first indicator was non-biologic therapy augmentation in LatAm (41.7%), IBD-related hospitalization in RME (UC: 50.7%; CD:37.3%) and in APAC for CD (39.1%), and anti-TNF discontinuation in APAC for UC (38.3%). Conclusion: Suboptimal response to anti-TNF agents is common in IBD patients in NICs. Observed regional differences in the incidence and indicators may reflect local practice and anti-TNF restrictions in IBD management. NCT Registration Number: NCT03090139.